To compare the efficacy of hyperbaric levobupivacaine (0.5%) versus hyperbaric bupivacaine (0.5%) in the subarachnoid block for infraumbilical surgeries - Rachna Gupta; Jitendra Agrawal; Preeti Goyal; Shreya Putta; Bharat Tarachandani (Asian Journal of Medical Sciences)
Background: Spinal anesthesia is the neuraxial regional anesthesia technique used in infraumbilical surgeries such as inguinal hernia, hydrocele, hysterectomy, and lower limb surgeries. Levobupivacaine and bupivacaine are local anesthetic agents used for spinal anesthesia.